How Does Firm Size and Capital Structure Affect Firm Value? - Radhika Putri Nursetya; Lina Nur Hidayati (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Objective: This paper explores whether the firm size and capital structure have an impact on corporate valuation. Then it will raise profitability as an intervening variable on the effect of company size and capital structure on corporate valuation. Research Design & Methods: Data gathering method is finalized by using the documentation method. In this study, data were obtained from published financial reports. Samples from this study were 30 manufacturing companies listed on the Indonesia Stock Exchange. Findings: The results exhibited that firm size affected profitability and firm value. In the meantime, the capital structure has a big influence on performance and does not affect the company's valuation. Profitability has a positive effect on corporate value. This study also concludes that profitability can mediate firm size to firm value. Conversely, profitability cannot mediate capital structure on corporate value. Implications & Recommendations: This study offers empirical evidence that profitability can be an intervening variable in firm size's effect on firm value. In further research, other variables can be added, which are considered to mediate company size and capital structure on corporate value. Contribution & Value Added: This study's results contribute to the financial literature, especially those related to public corporations' value in Indonesia. As a practical contribution, stockholders can use this study's outcomes as additional information in investment decisions.